Empirical Analysis of Data Mining Techniques for Social Network Websites - Fernando, S.G.S; MdJohar, Md Gapar; Perera, S.N. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Social networks allow users to collaborate with others. People of similar backgrounds and interests meet and cooperate using these social networks, enabling them to share information across the world. The social networks contain millions of unprocessed raw data. By analyzing this data new knowledge can be gained. Since this data is dynamic and unstructured traditional data mining techniques will not be appropriate. Web data mining is an interesting field with vast amount of applications. With the growth of online social networks have significantly increased data content available because profile holders become more active producers and distributors of such data. This paper identifies and analyzes existing web mining techniques used to mine social network data.